Investigating residents' perceptions of quality of urban life in Toul Kork, Phnom Penh, Cambodia - Mao, Seanghort (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2019)
This research examines the issue of quality of life and its correlation with social environment. This study utilized subjective approach as the direct effects of objective social dimensions on subjective assessments of social environment have been found to be weak. The study utilized seven life domains that contribute to the residents' quality of life (QOL). Sixteen hypotheses have been tested to investigate which life domains contribute the most and the least to residents' satisfactions with their quality of urban life (QOUL), and which domains and indicators are significantly related to one another. The assessment was collected via questionnaire survey with a sample of 200 respondents living in TK. The secondary data were obtained from desktop research, book, and Phnom Penh City Hall (PPCH). The frequency analysis found that the mean for overall QOUL in the neighborhood is “slightly good.” The mean for all life domains is “slightly satisfactory.” Spiritual life has the highest mean, while economic ability has the lowest mean. However, when the analysis distinguishes QOL from conventional QOUL domains, i.e. health and spiritual life are excluded; domain with the highest mean is home features, while the lowest mean is still economic ability. Similarly, correlation analysis found that spiritual life contributes the most to their overall QOUL while the least is economic ability. However, when spiritual life and health are excluded from correlation analysis, domain that contributes the most to overall QOUL is social involvement and community participation. Multiple regression analysis found that all domains contribute significantly to the neighborhood. Recommendations were made based on the findings – to improve safety through CPTED measures, to solve insufficient home parking by improving public transport system; and improving residents' home privacy through quality soundproof wall. Suggestions for further research have been made to improve similar type of study in the future.